Levels of health services audit proficiency among primary health care physicians from Comas district, 2018 - Guerra Uriarte, Erick Nelson (2021)
Objective: To identify the levels of health services audit proficiency among primary health care physicians from Comas district in 2018. Materials and methods: An analytical study was conducted. Out of a population of 110 physicians, 32 accepted to participate in the study. Sociodemographic variables and five types of health services audit proficiency were assessed: the first four were graded as “pass,” “in process” and “fail,” while the fifth was scored as “basic,” “intermediate” and “advanced.” The data was processed using SPSS Statistics statistical software version 24.00. Results: Sixty-two point five zero percent (62.50 %) of the study population consisted of attending physicians, while 37.50 % were medical chief officers. Males (68.80 %) prevailed over females (31.30 %). The global result of the levels of health services audit proficiency was “fail” (50.00 %), “in process” (43.80 %) and “pass” (6.25 %). Conclusions: Six point two five percent (6.25 %) of the study population achieved the “pass” score in the health services audit proficiency. The variables “tenure” (Sig. = 0.011) and “general training” (Sig. = 0.031) were significantly related to the development of health services audit proficiency.